A GENERAL LOOK AT THE VOCABULARY LEARNING AND TEACHING PROCESS IN FOREIGN LANGUAGE TEACHING - Ece SARIGÜL (Fırat University, 2019)
The aim of this study is to make suggestions for foreign language learners and teachers by investigating the methods and techniques used in the teaching of vocabulary which has a very important place to communicate and express ourselves in foreign language effectively. It is true that just knowing the meaning of a word is not enough for knowing exactly the word and its usage effectively. Knowing the characteristics of words such its pronunciation, spelling and sense relations to the other words is as important as in addition to knowing the meaning of a word. Firstly, several definitions of the word and the understanding of what does it mean to know a word in a language have been investigated by means of a detailed review of literature. There has been several researches and discussions which have been made in order to find the most useful methods and techniques for language teaching. The place and the importance of vocabulary teaching in common foreign language teaching methods and techniques are other subjects which we examined in our study. It is necessary to make use of language learning strategies and teach them by using appropriate techniques for sending them long term memory. It is clear that students are more successful who organize their learning processes than the other students. Thus, teachers should know about the language learning strategies themselves in order to help the students to choose and organize their learning processes. The use of appropriate techniques affect the vocabulary learning process and the words being permanent in the brain. The teaching of words by giving the students word lists and wanting them to memorize those lists or making word to word translation have some drawbacks. For this reason, some vocabulary teaching techniques such as visual techniques, oral techniques, dictionary use, use of context together with the use of technology have been examined and some suggestions have been made to the foreign language teachers which can be used for teaching vocabulary.